PENINGKATAN TATA KELOLA PASAR SRI BANTAS DESA CEPAKA - Komang Fridagustina Adnantara; Ni Luh Sili Antari (Synergy and Society Service, 2021)
Sri Bantas Traditional Market is one of the traditional markets located on Jl. Raya Munggu Br. Batanduren, Cepaka Village, Kediri District, Tabanan Regency. The objective in implementing this service is to provide assistance in the governance of the Sri Bantar Village market in Cepaka. The problems identified include: some traders in the Sri Bantas market have not implemented financial accounting practices, the lack of infrastructure arrangement in the Sri Bantas market, and the lack of a promotional strategy for traditional markets in the Sri Bantas market. The methods used in this assistance were interviews, observation, and data analysis. The work programs carried out in the Sri Bantas market were: 1) providing information about simple bookkeeping to market traders, 2) procuring hand washing stations, 3) procuring market block names , 4) data collection of traders, 5) making banners, and 6) making online pamphlets. The result of this activity is that some traders know the importance of making financial reports and how to make simple financial reports, up to date trader data has been inputted into the market system, the market is better known by the wider community.